Single Nucleotide Polymorphisms in IL8 and TLR4 Genes as Candidates for Digital Dermatitis Resistance/Susceptibility in Holstein Cattle. Issue 2 (3rd April 2017) - El-Shafaey, El-Sayed; Ateya, Ahmed; Ramadan, Hazem; Saleh, Rasha; Elseady, Yousef; Abo El Fadl, Eman; El-Khodery, Sabry
ABSTRACT: Relatedness between single nucleotide polymorphisms in IL8 and TLR4 genes and digital dermatitis resistance/susceptibility was investigated in seventy Holstein dairy cows. Animals were assigned into two groups, affected group (n = 35) and resistant group (n = 35) based on clinical signs and previous history of farm clinical records. Blood samples were collected for DNA extraction to ampliy fragments of 267-bp and 382-bp for IL8 and TLR4 genes, respectively. PCR-DNA sequencing revealed three SNPs in each of IL8 and TLR4 genes. The identified SNPs associated with digital dermatitis resistance were C94T, A220G, and T262A for IL8 and C118T for TLR4. However, the G349C and C355A SNPs in TLR4 gene were associated with digital dermatitis susceptibility. Chi-square analysis for comparison the distribution of all identified SNPs in both IL8 and TLR4 genes between resistant and affected animals showed no significant variation among the identified SNPs in IL8 gene. Meanwhile, there was a significant variation in case of TLR4 gene. As a pilot study, the present results revealed that identified SNPs in IL8 and TLR4 genes can be used as a genetic marker and predisposing factor for resistance/susceptibility to digital dermatitis in dairy cows. However, TLR4 gene may be a potential candidate for such disease.